COMMISSIVE SPEECH ACT ON TIM COOK’S INTERVIEW IN OXFORD UNIVERSITY - Putri, Viola Rahmi; Merina, Yola; Alicia, Dona (Universitas PGRI Sumatera Barat, 2021)
This research was conducted to know the kind of commissive and act the analysis of the three acts which are locution, illocution and perlocution could be found in the interview of Tim Cook in Oxford University. This research was a qualitative research. The source of data that used in this research was a video of an interview while the data which would be analyzed were utterances of the speakers in the interview. The research result was showed that there were two forms of commissive act that can be found in the interview which are promise and volunteering acts. From the result, it can be concluded that the use of promise act form was mostly act used during the interview of Tim Cook in Oxford University. This form was used by the interviewer when giving instruction during the interview or when asking question to Tim. Meanwhile the volunteering form was used when Tim volunteering himself to give an example to the audience of the interview.